Impact of food safety regulations on agricultural trade: Evidence from China's import refusal data. (December 2021) - Sun, Dongsheng; Liu, Yifang; Grant, Jason; Long, Yanyu; Wang, Xiaojuan; Xie, Chaoping
Highlights: China's evolving food safety regulations generally restrict trade. Regulations have a larger trade impeding effect on exporters with lower food safety standards compared to exporters with higher-food safety standards. The size of the negative trade growth effect depends critically on the importing firms' ownership structure and the type of import refusals. SOE import purchases in China are more affected by import refusal measures due to safety and hygiene reasons, whereas SOE imports are little impacted by refusals for non-safety and hygiene reasons. Abstract: Recent food safety incidents, such as melamine in infant milk powder, have contributed to Chinese consumers' growing food safety concerns. Spurred by these challenges, the Chinese government passed a series of laws and regulations to enhance food safety, which have the potential to impact China's food imports. In this paper, we provide a detailed overview and quantification of the impact of China's evolving food safety regulations on food imports. Specifically, we document the landscape of non-tariff measures driven by changes in China's food safety regulations and demonstrate that China has been building a more comprehensive regulatory system with food safety legislations becoming more stringent and cohesive. We then quantify the impact of food safety regulations on China's food imports using a novel dataset of China's import refusals. Our results show that China's evolving food safety regulations generally restrict trade, reducing imports by 2.24%, on average, for countries with low food safety regulations compared to 0.78% for countries with higher food safety standards. Further, the asymmetry between countries with lower food safety standards and China's evolving food safety standards is growing over time. At the firm level, China's border rejections have also had a significant and negative impact on the growth rate of import value. A 1% increase in the number of import refusals caused by safety and hygiene reasons decreases the average growth rate of import value by 4.51%. Importantly, because state-owned enterprises (SOEs) assume more social responsibilities and value their reputation within the context of Chinese policy, they are more affected by China's import refusal measures than non-SOEs.